Revving the engine: PKB/AKT as a key regulator of cellular glucose metabolism - Li, Xia; Hu, Shuying; Cai, Yaoting; Liu, Xuelian; Luo, Jing; Wu, Tao (Frontiers in Physiology, 2024)
Glucose metabolism is of critical importance for cell growth and proliferation, the disorders of which have been widely implicated in cancer progression. Glucose uptake is achieved differently by normal cells and cancer cells. Even in an aerobic environment, cancer cells tend to undergo metabolism through glycolysis rather than the oxidative phosphorylation pathway. Disordered metabolic syndrome is characterized by elevated levels of metabolites that can cause changes in the tumor microenvironment, thereby promoting tumor recurrence and metastasis. The activation of glycolysis-related proteins and transcription factors is involved in the regulation of cellular glucose metabolism. Changes in glucose metabolism activity are closely related to activation of protein kinase B (PKB/AKT). This review discusses recent findings on the regulation of glucose metabolism by AKT in tumors. Furthermore, the review summarizes the potential importance of AKT in the regulation of each process throughout glucose metabolism to provide a theoretical basis for AKT as a target for cancers.